Exploring differences in FFCO2 emissions in the United States: comparison of the Vulcan data product and the EPA national GHG inventory - Anna Kato; Kevin R Gurney; Geoffrey S Roest; Pawlok Dass (Environmental Research Letters, 2023)
Quantitative assessment of greenhouse gas emissions is an essential step to plan, track, and verify emission reductions. Multiple approaches have been taken to quantify U.S. CO _2 emissions from fossil fuel combustion (FFCO _2 ), the primary driver of global climate change. A 2020 study analyzing atmospheric ^14 CO _2 observations (a key check on bottom-up estimates) and multiple inventories found significant differences in the U.S. total FFCO _2 emissions. The specific reasons for the differences were left for future work. Here, we take up this task and explore the differences between two widely used U.S. FFCO _2 inventories, the Vulcan FFCO _2 emissions data product and the Environmental Protection Agency (EPA) GHG inventory, developed using mostly independent data sources. Where possible, we isolate definitions and data sources to quantify/understand discrepancies. We find that the initial 2011 emissions difference (104 MtC yr ^−1 ; RD = 10.7%) can be reduced by aligning the two estimates to account for differing definitions of emission categories or system boundaries. Out of the remaining 90.6 MtC yr ^−1 gap (RD = 6.2%), we find that differences can be largely explained by data completeness, emission factors, and fuel heating values. The remaining difference, 45.4 MtC yr ^−1 (3.2%), is difficult to isolate due to limited EPA documentation and disaggregation of emissions by sector/fuel categories. Furthermore, the final net difference obscures countervailing gross differences (∼40 MtC yr ^−1 ) within individual sectors. Nevertheless, this comparison suggests the potential for a national estimation approach that can simultaneously satisfy reporting at the national/global scale and the local scale, maintaining internal consistency throughout and offering detailed decision support to a much wider array of stakeholders.